The assessment of the thermal necrosis due a drilling dental process with or without irrigation - Fonseca, E.M.M. (2013)
Main goal of this work is to present a numerical model to study the thermal necrosis due a dental drilling process, with and without water irrigation. Also an experimental methodology is used to measure the thermal occurrence in a pig mandible.